HUA NAI RANG :SOCIAL COMMUNICATION THROUGH FOLK LITERATURE - BOORANASAKAWEE, WEERINPHAT; NAKDONTREE, UDOMWIT; SUPA, CHIRAPA; SRIHATA, TANIYABHORN (Journal of Suan Sunandha Arts and Culture, 2023)
A research study on Hua Nai Rang : Social Communication through Folk Literature have a purpose To study and analyze social communication through southern folk literature titled Hua Nai Rang. This is a qualitative research. by collecting field data From interviews and observations There is a group of informants, namely people in the community, people who participated in the ritual. and local philosophers then collect information be analyzed and synthesized to compile descriptively The results showed that Communicating in a variety of social contexts through literature as follows: 1. Beliefs and beliefs which appears in the form of a sacred space The symbol of the sculpture "Great-grandfather Mr. Rang" and monuments in architecture "Hin Hua Nai Rang" to commemorate the heroes and is evidence that reflects the beliefs and beliefs of the people in the community and sacrifice until causing the traditions and practices to continue There are characteristics of a combination of animism. and the beliefs of Buddhism live together Create expectations, symbols and positive energy for people in the community. This southern folk literature also inserts the strength of the culture and the way of life of the community. including the symbols, traditions and identity of the South clearly